Self‐administration of icatibant in acute attacks of Type I hereditary angioedema: A case report and review of hereditary angioedema. Issue 6 (28th October 2019) - Piras, Viviana; Alves, Francisca; Gonçalo, Margarida
Abstract: Hereditary angioedema (HAE) is a rare group of genetic disease characterized by non‐itchy swelling of subcutaneous and submucosal tissues of the extremities, genitalia, gastrointestinal tract, and upper airways, which can be life threatening. Moreover, unpredictability and recurrence of HAE attacks significantly affect patients' quality of life. Short‐ and long‐term prophylaxis is used to decrease the severity and frequency of attacks, but during severe or potentially severe acute episodes, treatment with C1‐INH replacement or icatibant is mandatory. Icatibant is a selective bradykinin B2 receptor antagonist that has been licensed for self‐administration at home, resulting in earlier treatment of the attack and quicker recovery, less emergency admittance with a significant improvement of patients' quality of life, and decrease of health care costs. The authors present a case of a young woman, affected by Type I HAE, who has been successfully treated with icatibant on demand at home, resulting in reduction of emergency admissions and improvement of quality of life. The authors also review the different types HAE, their clinical aspects, diagnosis, and management.